From 0D to 3D: Dimensional Control of Bismuth for Potassium Storage with Superb Kinetics and Cycling Stability. Issue 40 (23rd September 2021) - Cheng, Xiaolong; Sun, Yingjie; Li, Dongjun; Yang, Hai; Chen, Fei; Huang, Fanyang; Jiang, Yu; Wu, Ying; An, Xingtao; Yu, Yan
Abstract: Bismuth‐based anode for potassium ion batteries (KIBs) has gained great attention due to its high volumetric specific capacity (3800 mA h mL −1 ). However, the Bi‐based materials face a huge volumetric change upon the cycling process. Herein, the dimensionality manipulation in the Bi‐anode is focused to realize superior electrochemical performance. The morphological evolution rules of 0D, 1D, 2D, and 3D Bi anodes upon the potassiation/depotassiation process are clarified. Thereinto, the 2D‐Bi transforms into the continuous porous Bi nanoligaments with retaining the original nanosheet shape, which shorten the ion diffusion path and buffers the volume expansion, demonstrating the best electrochemical performance. The 2D‐Bi achieves a superior long‐term cycling stability (344 mA h g −1 after 750 cycles at 10 A g −1 ) and excellent rate performance (345 mA h g −1 at 30 A g −1 ). The full‐cell paired with Prussian blue (2D‐Bi//PB) exhibits high energy density and power density (174 W h kg −1 at 475 W kg −1 ). The operando X‐ray diffraction reveals that the final alloyed product is hexagonal‐K3 Bi at first cycle, while cubic‐K3 Bi is obtained in the following cycle. This strategy is helpful to design alloy‐type anodes for practical application in KIBs. Abstract : The morphological evolution rules of Bi with different dimensionality upon the potassiation/depotassiation process are clarified. Thereinto, the 2D‐Bi transforms into the continuous porous Bi nanoligaments with retaining the original nanosheet shape, which shortens the ion diffusion path and buffers the volume expansion, leading to the best rate performance and superior long‐term cycling stability.